Exploring the inner path: a comprehensive literature review on self-engagement behaviour and its impact on business-oriented social media content / Tuan Putri Raidah Tuan Rosedi, Noorlida Daud, Mat Redhuan Samsudin - Tuan Rosedi, Tuan Putri Raidah; Daud, Noorlida; Samsudin, Mat Redhuan (Universiti Teknologi MARA, Perak, 2024)
Social media serves as a widely utilized channel for communication between businesses and individuals. Self-engagement on social media is a crucial aspect of online behaviour, shaping both individual experiences and digital communities. Hence, this paper focuses on the layout content and its contribution to cognitive processes in relation to users' self-engagement. The methodology employed in this paper is literature-based, with data collected from numerous sources. The findings suggest that the Elaboration Likelihood Model (ELM) can serve as a theoretical framework, providing an understanding of persuasion mechanisms via peripheral routes. This model holds particular significance in the realm of self-engagement, where users interact with content using diverse cognitive processes. Social media platforms have the capacity to adjust and improve their features to align with user preferences, ensuring a more fulfilling and satisfying user experience. By employing successful tactics grounded in theoretical frameworks such as the ELM, companies and individuals can refine their strategies for engagement and communication on social platforms.